Body Matched Antennas for Microwave Medical Applications - Li, Xuyang (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2013)
In this work, new concepts of body-matched antennas for microwave medical applications were developed, where the antennas are placed directly on or in the human body. Two types of antennas were designed - on-body matched antennas for diagnosis and implantable antennas for data telemetry with the main focus of miniaturization yet maintained a high radiation performance. The applicability of the antennas was verified using a medical imaging system for the detection of hemorrhagic stroke.